1983
DOI: 10.2307/280559
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Maya Chert Workshops in Northern Belize, Central America

Abstract: Recent archaeological work at Colha and at other localities in the geographically restricted chert-bearing zone of northern Belize has revealed large-scale exploitation of chert for stone tool production. Workshops dated during the Late Preclassic period signal the beginning of craft specialization in chert working that continued in the Late Classic and into the Early Postclassic periods. Secular items such as large oval bifaces, tranchet bit tools and prismatic blades, as well as nonsecular eccentrics and ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 6 publications
1
100
0
Order By: Relevance
“…Since chert artfiacts are distributed relatively evenly across the site and since the total number of chert artifacts is minuscule compared to sites where surplus production of chert tools has been documented (e.g., Shafer and Hester 1983), we conclude that we have not found any specialized chert tool manufacturing at Chunchucmil.…”
Section: Lithicsmentioning
confidence: 58%
See 1 more Smart Citation
“…Since chert artfiacts are distributed relatively evenly across the site and since the total number of chert artifacts is minuscule compared to sites where surplus production of chert tools has been documented (e.g., Shafer and Hester 1983), we conclude that we have not found any specialized chert tool manufacturing at Chunchucmil.…”
Section: Lithicsmentioning
confidence: 58%
“…However, several studies have shown that resources in the Maya lowlands are not as evenly dispersed as once thought (Dunning et al 1998;Fedick 1996;gomez Pompa et al 2003;McAnany 1993). Lowland resources such as salt (A. P. Andrews 1983;McKillop 2002), chert (Potter and King 1995;Shafer and Hester 1983), and cacao (McAnany et al 2002) are famously patchy. But even in areas without such assets, other features such as escarpments , swamp edges (Kunen 2004), karst depressions (Kepecs and Boucher 1996;Munro Stasiuk and Manahan 2010), rivers (Siemens 1996), terrace-able hills (Chase and Chase 1998), and fracture zones (Fedick et al 2000) each permit local resource specializations.…”
Section: Definitions and Delays In Economic Anthropologymentioning
confidence: 99%
“…The bi face from the "Puleston axe" is virtually identical in technology and form to the Late Preclassic large oval bifaces produced in the chert workshops at Col ha (fig 3;Shafer 1979;Shafer and Oglesby 1980;Shafer and Hester 1983). Oval bifaces were made at Col ha as early as the Middle Preclassic but were smaller and more crudely fashioned.…”
Section: Descriptionmentioning
confidence: 84%
“…Moreover, some traits are similar to those on early preceramic points from North America (Justice 1987). Although this biface fragment is stemmed, it is also different from the stemmed and barbed points from the Late Archaic in Belize and all Maya Preclassic, Classic, and Postclassic point types (Lohse et al 2006;MoholyNagy 2003;Rovner and Lewenstein 1997;Shafer and Hester 1983;Stemp and Awe 2013;Willey et al 1965).…”
mentioning
confidence: 90%